Os princípios pedagógicos presentes na legislação do ensino médio e da educação profissional após a LDB Nº 9394/96 - Becker, Daiane Acco Rossarola (2015)
The main objective of the current research consists of analyzing pedagogical principles that support the student education present in the legislation of High School and of Technical Vocational Education of Medium Level after the LDB (Law of Directives and Basis for National Education) 9394/96. The study also aims: a) to analyze the relationship between State, capitalist productive System and Education, verifying how the High School and the Vocational Education articulate themselves in this context; b) to identify the pedagogical principles that guide the education of the subjects contained within the legislation inherent to High School and Technical Vocational Education of Medium Level; c) ascertain the tendencies of education inherent to legal documents destined both to High School as well as to Technical Vocational Education of Medium Level. The research is characterized as documentary bibliography. This work is structured in an introduction, three chapters and the final considerations. Among other resulting evidences from this study, it is noted that the principles of employability, competences and flexibility support the Decree n. 2.208/97, the Law n. 12.513 (PRONATEC) and the National Curricular Guidelines for the Technical Vocational Education of Medium Level. Opposing these principles, the work has as the educational principle supporting the Decrees n. 5154/04 and n. 5.840/06, the Base Document of PROEJA (2007), the National Curricular Guidelines for High School and the Orientation document of Innovating High School. The study shows that these principles support a tendency of education; the ones of employability, competences and flexibility, for example, support a more fast-forward and fragmented formation, tending to the specific purpose of sending manpower to the labor market, while the work as the educational principle supports a whole formation of the human being, a formation that enables the comprehension of fundamental dimensions of life which structure the social practice.